Modeling the impact of green energy consumption and natural resources rents on economic growth in Africa: An analysis of dynamic panel ARDL and the feasible generalized least squares estimators - Sulemana Mumuni; Thomas Mwimba (Cogent Economics & Finance, 2023)
The United Nations Sustainable Development Goals (SDGs) 7, 11, and 12 are all aimed at advancing green energy consumption in the fight against the three planetary crises facing the world today: climate change, biodiversity loss, and pollution. Besides, Africa has an abundance of natural resources, yet, the continent continues to witness slow growth and development compared to its counterparts. Therefore, this study, the first of its kind, simultaneously assesses the impact of green energy consumption and natural resources rents on economic growth by applying the dynamic panel ARDL and the Feasible Generalized Least Square (FGLS) estimators on data from 1990 to 2020 for 24 selected African countries. The results show that green energy consumption has a short-run growth-limiting and a long-run growth-enhancing effect in Africa. Also, CO2 emissions have both short- and long-run significant positive impacts on economic growth, while fossil fuel combustion negatively impacts growth both in the short and long run, albeit the effect is not significant in the long run. Similarly, regarding Africa's natural resource rents' impact on growth, the results show that total natural resource rents are growth-enhancing in the short run and growth-limiting in the long run. Additionally, both forest and mineral rents have a significant short-run negative impact on growth in Africa. However, in the long run, only the effect of mineral rent is growth-enhancing although generally not statistically significant. These findings provide relevant implications for policy shifts to enhance environmental sustainability, achieve sustainable economic growth, and ensure proper natural resources management in Africa.
Keywords: 330; Economic growth; Green energy; Natural resource rents; Panel estimation; SDGs